Personal characteristics of predisposition to destructive behavior - I. M. Plugina; E. G. Abakarova; A. S. Lukyanov (Кардиоваскулярная терапия и профилактика)
Aim. To identify personal characteristics determining the subject’s destructive behavior.Material and methods. Students from Stavropol State Medical University and North-Caucasus Federal University (n=609) took part in the study. The following diagnostic methods were used: a tendency to abnormal behavior (A. N. Orel), a meaning-life orientation test (D. A. Leontyev), a self-attitude test (S. R. Panteleev), a self-organization of activity questionnaire (E. Yu. Mandrikova).Results. We established that the sample corresponds to the characteristics of age-psychological and socio-professional development. The greatest severity by type of deviant behavior was found among respondents who are prone to overcoming norms and rules, and among those who have a reduced tendency to control emotional reactions. The least pronounced were tendencies to delinquent and addictive behavior, the tendency to aggression and violence. The dominant trends in this context are students’ understanding of the emotional richness of their ives, and the average psychological portrait of the respondent reflects their focus on themselves when implementing life’s tasks. On average, students are open to change, accept and value themselves, focus on their own strengths when planning and implementing future activities. They are focused on the present, understand the need to define the goals in life and activity. The study of individual parameters of personal characteristics and the severity of destructive behavior types made it possible to describe models of the relationship between these phenomena.Conclusion. The study showed that the current situation in the development of society is accompanied by risk factors that cause states of emotional stress and maladaptation, which has a negative impact on mental health and behavior. Diagnosis of personal characteristics and the severity of destructive behavior types in students made it possible to describe models of the relationship between these phenomena through regression analysis. A reflexive analysis of the results obtained made it possible to reveal an invariant part of personal characteristics in models of destructive behavior and the presence of certain personal characteristics that can manifest themselves in the variable part of a model of destructive behavior.